Academic intrinsic motivation and perceived academic competence in Greek elementary students with and without learning disabilities - Zisimopoulos, Dimitrios A.; Galanaki, Evangelia P. (Learning Disabilities Research & Practice, 2009)
The aim of this study was to examine differences in intrinsic motivation and perceived academic competence as well as in their association between 5th- and 6th-grade students with learning disabilities (LD) (n = 40) and their typically achieving peers. Participants were 980 Greek elementary students from the metropolitan area of Athens. As predicted, students with LD showed lower intrinsic motivation and perceived academic competence than students without LD almost across all subscales. Exceptions were noticed in intrinsic motivation concerning curiosity/interest and history subscales as well as perceptions of academic competence in the subjects of history and science. Support was found that among typically achieving students intrinsic motivation was positively and significantly related at a moderate level to perceived academic competence across all subscales, as opposed to students with LD, for whom few correlations were found.